2021
DOI: 10.1002/deo2.44
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging versus white light for detecting sessile serrated lesion: A prospective randomized multicenter study

Abstract: Objectives Colonoscopy is the gold standard diagnostic test used to detect early colorectal lesions and prevent colorectal carcinoma. Narrow band imaging (NBI) is an imaging technique that provides improved image resolution of the mucosa during endoscopy. Whether NBI improves the detection of sessile serrated lesion (SSL) is controversial—our aim was to assess this during routine colonoscopy. Methods We conducted a multicenter, prospective, randomized, controlled trial.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The subanalyses in a recent meta‐analysis including six prospective RCTs showed a significant difference in favor of NBI in the odds of detecting at least one nonadenomatous polyp in the proximal colon (OR 1.35, 95% CI 1.05–1.74; P = 0.02), which points toward an increase in SSLDR 19 . However, a recent prospective RCT with a primary endpoint setting of SSLDR showed no additional value of NBI observation over WLI for detection of SSLs (7.5% NBI vs. 8.0% WLI; P = 0.852) 55 . A prospective tandem RCT showed that NBI and WLI yielded a similar detection rate of HPs and SSLs (HP: 18 vs. 19, SSL: 6 vs. 5, not significant) among patients diagnosed with serrated polyposis syndrome (SPS), 56 while another prospective tandem RCT similarly showed no differences in the SSLDR (NBI 47.4% vs. WLI 51.9%, OR 0.84, 95% CI 0.37–1.91) among patients without SPS 57 .…”
Section: Detection Of Colorectal Polyps Using Nbimentioning
confidence: 98%
See 1 more Smart Citation
“…The subanalyses in a recent meta‐analysis including six prospective RCTs showed a significant difference in favor of NBI in the odds of detecting at least one nonadenomatous polyp in the proximal colon (OR 1.35, 95% CI 1.05–1.74; P = 0.02), which points toward an increase in SSLDR 19 . However, a recent prospective RCT with a primary endpoint setting of SSLDR showed no additional value of NBI observation over WLI for detection of SSLs (7.5% NBI vs. 8.0% WLI; P = 0.852) 55 . A prospective tandem RCT showed that NBI and WLI yielded a similar detection rate of HPs and SSLs (HP: 18 vs. 19, SSL: 6 vs. 5, not significant) among patients diagnosed with serrated polyposis syndrome (SPS), 56 while another prospective tandem RCT similarly showed no differences in the SSLDR (NBI 47.4% vs. WLI 51.9%, OR 0.84, 95% CI 0.37–1.91) among patients without SPS 57 .…”
Section: Detection Of Colorectal Polyps Using Nbimentioning
confidence: 98%
“…19 However, a recent prospective RCT with a primary endpoint setting of SSLDR showed no additional value of NBI observation over WLI for detection of SSLs (7.5% NBI vs. 8.0% WLI; P = 0.852). 55 A prospective tandem RCT showed that NBI and WLI yielded a similar detection rate of HPs and SSLs (HP: 18 vs. 19, SSL: 6 vs. 5, not significant) among patients diagnosed with serrated polyposis syndrome (SPS), 56 while another prospective tandem RCT similarly showed no differences in the SSLDR (NBI 47.4% vs. WLI 51.9%, OR 0.84, 95% CI 0.37-1.91) among patients without SPS. 57 Although favorable outcomes for NBI in the detection of proximal SLs were reported, the difference was not significant (NBI 204 vs. WLI 158; P = 0.085).…”
Section: Detection Of Sessile Serrated Lesions (Ssls)mentioning
confidence: 99%
“…Numerous studies compare white light and NBI in detecting polyps. Based on prior research, the detection rate of SSL is estimated to be around 7.5% with NBI and varies between 6.8% and 8.0% with white light endoscopy, although no statistically significant difference has been observed ( 15 18 ). NBI is believed to be more effective for visual diagnosis rather than polyp detection.…”
Section: Serrated Polypsmentioning
confidence: 99%
“…A multicenter RCT reported that the differences between NBI and HD-WLE were not remarkable in detection rates of SSL (7.5% NBI vs. 8.0% HD-WLE, p =0.852), ADR (41.0% NBI vs. 37.5% HD-WLE, p =0.531), and PDR (61.0% NBI vs. 54.0% HD-WLE, p =0.157). 29 Another study investigated residual SSA detection using NBI after endoscopic resection. All lesions were randomized into the NBI and WLE groups to detect remnant tissue on the resected margin.…”
Section: Narrow-band Imagingmentioning
confidence: 99%